FACULTY QUALIFICATIONS ACROSS THE VERTICALLY-ARTICULATED COLLEGES OF CEBU NORMAL UNIVERSITY IN THE PHILIPPINES: THE POLICY FRAMEWORK - Lapiz, Gary B. (European Scientific Journal, ESJ, 2015)
This is a technical research paper which aims to present the policy framework of Cebu Normal University, a state-owned university in the Philippines, regarding faculty qualifications across its â€œvertically articulated collegesâ€ to meet in its attempt at par global educational standards.